Changes in vitamin D status among adults from the COVID-19 pandemic to post-pandemic normality - Chen, Yanzhao; Kong, Guilian (Frontiers in Nutrition, 2024)
Introduction The COVID-19 pandemic has prompted widespread lockdown measures globally, significantly impacting daily activities and outdoor exposure. This study investigates the effect of the pandemic on vitamin D levels and the prevalence of vitamin D deficiency in the adult population, with a focus on gender-specific differences. Methods A total of 1525 adults from Henan Provincial People’s Hospital were included. Serum 25-hydroxyvitamin D (25(OH)D) levels were measured using the Elecsys® Vitamin D total kit on the Roche Cobas® 8000 analyzer. The Clinical Application Consensus on Vitamin D and Its Analogs defined deficiency as 25(OH)D levels below 20 ng/ml. Statistical analysis was performed using SPSS 23.0 and GraphPad Prism 8 software. Results The overall 25(OH)D levels increased from 18.14 ng/ml [IQR: 13.78, 23.68] in 2022 to 19.15 ng/ml [IQR: 14.88, 25.01] in 2023 (p=0.004). Males exhibited significant improvement in 25(OH)D levels from 18.01 ng/ml [IQR: 14.10, 23.53] in 2022 to 20.49 ng/ml [IQR: 16.11, 26.01] in 2023 (p<0.001). The prevalence of vitamin D deficiency decreased from 62% in 2022 to 54.9% in 2023 (p=0.009), with a notable reduction in males (64.1% in 2022 to 47.2% in 2023). Among 168 individuals tested in both years, 25(OH)D levels increased from 20.73 ± 9.37 ng/ml in 2022 to 22.28 ± 8.59 ng/ml in 2023 (p=0.012), and the deficiency rate decreased from 58.3% in 2022 to 47.0% in 2023 (p=0.038). The 40–49 age group showed significant improvement in 25(OH)D levels from 16.10 ng/ml [IQR: 12.41, 21.18] in 2022 to 18.28 ng/ml [IQR: 13.91, 23.86] in 2023 (p=0.005), with a reduction in deficiency rate from 72.8% to 59.9% (p=0.02). Furthermore, in February, March, and April, 2022, 25(OH)D levels were significantly lower compared to 2023 (p<0.001, p=0.002, p<0.001, respectively), accompanied by a higher prevalence of vitamin D deficiency (p<0.001, p=0.015, p<0.001, respectively). Discussion This study demonstrates that the COVID-19 pandemic significantly impacted vitamin D levels, leading to an increased prevalence of deficiency, particularly among males. These findings highlight the critical importance of maintaining sufficient outdoor activities to ensure adequate vitamin D levels. The data underscore the need for public health strategies to address potential deficiencies during prolonged periods of limited outdoor exposure.